2009
DOI: 10.1177/1088357609332675
|View full text |Cite
|
Sign up to set email alerts
|

Postsecondary Educational Aspirations of High-Functioning Adolescents With Autism Spectrum Disorders and Their Parents

Abstract: Individual interviews with 21 high-functioning adolescents diagnosed with an autism spectrum disorder and their parents were used to assess postsecondary educational aspirations and thoughts concerning obstacles and resources that shape educational achievement of this group. The results from these semistructured interviews revealed that both the adolescents and their parents have clear postsecondary educational goals but have significant concerns about the readiness of postsecondary institutions to meet the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 15 publications
4
110
0
3
Order By: Relevance
“…In line with Camarena and Sarigiani (2009) who conducted a qualitative research on the aspirations of students with ASD and their parents about post-secondary education, it is highly striking that students with ASD were more concerned about dealing with their social rather than with academic challenges. Students realized how important having a social network is in order to feel a sense of belonging.…”
Section: Discussionmentioning
confidence: 96%
“…In line with Camarena and Sarigiani (2009) who conducted a qualitative research on the aspirations of students with ASD and their parents about post-secondary education, it is highly striking that students with ASD were more concerned about dealing with their social rather than with academic challenges. Students realized how important having a social network is in order to feel a sense of belonging.…”
Section: Discussionmentioning
confidence: 96%
“…Even though some recognize that they differ from their peers, there is wide variance in their levels of self-awareness and acceptance of being "disabled" [29]. Studies have shown that most teenagers with autism do not perceive their diagnosis as a disability [30], and some scholars have also argued that autism is not a disability but rather a neuro-cognitive variation [31].…”
Section: International Journal Of Information and Educationmentioning
confidence: 99%
“…Sadly, many college students with ASD may lack the initiative or self-advocacy skills needed to seek these resources because of social deficits, anxiety, immaturity, and sometimes passive-dependent temperament (Anckarsäter et al, 2006;Soderstrom et al, 2002). Although a growing number of colleges offer support programs for students with ASD (Zager & Alpern, 2010), some students may view supports as stigmatizing or unhelpful and prefer not to enroll in special programs despite their parents' wishes (Camarena & Sarigiani, 2009). Conflicting priorities arise from the trend that parents often consider their child's skill deficits most salient in college planning considerations, such as availability of social support and mentoring, while transitional youth with ASD may place greater value on environmental concerns such as the coursework and campus disability awareness (Camarena & Sarigiani, 2010).…”
Section: Educationmentioning
confidence: 99%